The effect of stage of maturity on the nutritive value of smooth bromegrass and eastern gamagrass silages - J.E. Turner; M.K. Siefers; G.L. Huck; S.A. Anderson; K.K. Bolsen; Matthew A. Young (Kansas Agricultural Experiment Station Research Reports, 1997)
Early- and late-harvested smooth bromegrass and eastern gamagrass silages and fourthcutting alfalfa silage were compared in two, 20- day voluntary intake and digestion trials. Visual appraisal and pH values indicated that all five forages were well preserved as silage. Voluntary intake tended to be higher for sheep fed bromegrass and alfalfa silages compared to those fed gamagrasssil ages. The late-harvested gamagrass silage had the lowest DM intake in both periods. Dry matter, crude protein, and neutral detergent fiber digestibilities were generally similar for the two grasses within the early- and late-harvested silages. Chemical analyses indicated that the two bromegrass silages were of nearly equal nutritive value; however, digestion trial results showed that the early-harvested silage was higher in quality than the late-harvested silage. Results of both chemical analyses and digestion trials showed that the early-harvested gamagrass silage was higher in quality than the late-harvested silage.
Keywords: Cattlemen& #x27; s Day; 1997; Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 783; Beef; Grass; Smooth brome; Eastern Gama; Silage